Assessment of Psychological Problems for Institutionalized and Noninstitutionalized Geriatric People in Baghdad City - Al-Elaiawy, Abdullah; Mohammed, saja (Iraqi National Journal of Nursing Specialties, 2006)
objective : To assess for Psychological Problems. The study was carried out from 1st of December 2004 to 15th March, 2005. Mythology : A descriptive comparative study was conducted for elder in the geriatric home and the community; A questionnaire was constructed to achieve the purposes of the study; it includes two parts dealing with the elder demographic characteristics and psychological problems. A purposive (no probability) sampling of (100) elderly include (50) elderly from the Geriatric Home and (50) elderly from the community. Data were collected and analyzed through a descriptive statistical approach (frequency, percentage, mean and mean of scores, Standard deviation, Relative Sufficiency). Result : the study concluded that Most of institutionalized geriatric people suffer from psychological problems (Cognitive disorders( Sever Amnesia (RS(73.33%)), Mental confusion (RS(71.33%));Anxiety (RS(88%)); Depression (Sever sadness (RS(84.67%)); Anger(RS(94.67%)) ; and Low self-esteem (Feeling of in confidence about future (RS(75.33%)) more than those who live in noninstitutionalized. The study recommended that families who were caring for elderly person should receive financial support from government and establishing geriatric centers for dealing with special medical, and psychological problems...